Estudando física através dos exercícios realizados nas academias de musculação de Breves-PA - LEITE, Anderson Corrêa (2024)
Biomechanics is one of the best areas of biophysics that provides a deeper understanding of the movement of the human body, because the human skeleton is a system of components or levers, in which bone can be visualized as a rigid bar that can transmit and modify force and movement. The forces exerted on the body (including muscle forces) have components that tend to produce not only rotational movements as translational joints of the human body, even when performed in small magnitudes are important for understanding the stress and joint stability. The knowledge of the possible safe and each joint of the human body movements as well as the degrees of each joint range of motion, provides a guideline for proper biomechanical analysis. Thus, when the arm of the force (weight and muscle) and the axis of motion (joint) changes throughout the movement directly affects the torque. In this work we try to show how physical principles can describe and promote the implementation of a weight training exercise in gyms Brief in order to have a good efficiency without concern for injury.